Resilience of the Traditional Shoe Industry Amid Global Competition: An Empirical Study of Asyifa Lexus Jawa Shoes Cibaduyut Store - Cut Merlinda Shintya P; Tazkia Amelia Rahmat; M Fauzan Fahriyadi; Sofia Oktavia Dewi Fasha; Muhamad Agung Aropah; Kania Indah Sari (Journal of Economic and Business Advancement, 2026)
This study examines the resilience of the traditional footwear industry amid intensifying global competition through an empirical case study of Asyifa Lexus Jawa Shoes in Cibaduyut, Indonesia. Employing a qualitative descriptive approach, the research draws on in-depth interviews and direct observation to analyze how changing consumer preferences, digital marketplaces, and imported footwear influence business sustainability. The findings reveal that declining interest in handmade leather shoes among younger consumers has pressured traditional producers to reconfigure their strategies. Asyifa Lexus Jawa Shoes responds through continuous design adaptation aligned with global trends, differentiation via customized shoe production, and specialization in institutional safety footwear for the Indonesian National Armed Forces and National Police. These strategies reduce exposure to price-based competition and create stable, trust-based market relationships. The study contributes to the literature on industrial and SME resilience by demonstrating how traditional enterprises can survive globalization through focused differentiation, dynamic capabilities, and niche market penetration. Practically, the findings offer strategic insights for traditional footwear SMEs seeking to maintain competitiveness while preserving artisanal identity.